2018
DOI: 10.1108/md-10-2016-0713
|View full text |Cite
|
Sign up to set email alerts
|

Organizational climate and job satisfaction: do employees’ personalities matter?

Abstract: Purpose The purpose of this paper is to provide some insights on the interplay of organizational climate and job satisfaction, taking personality traits as a moderator. Design/methodology/approach The paper reviews the extant literature from which it develops a theoretical model which is then tested empirically in the Malaysian context, using hierarchical regression methodology. Findings The results imply that there are moderating effects of personality traits on the relationship between certain aspects of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
72
0
15

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(89 citation statements)
references
References 57 publications
(72 reference statements)
2
72
0
15
Order By: Relevance
“…For example, Chen and Spector [62], Brockner [63], and De Cremer [64] have shown that negative leader-employee interactions have a negative influence on the employees' satisfaction, which results in signs of stress and unwillingness to go to work. Tsai [65], Hashemi and Sadeqi [41], Ángel Calderón Molina et al [66], and Ahmad et al [67] predict that the organizational climate has a significant effect on job satisfaction. In this paper, we introduce work style as a mediator.…”
Section: Mediator Between Organizational Climate and Job Satisfactionmentioning
confidence: 99%
“…For example, Chen and Spector [62], Brockner [63], and De Cremer [64] have shown that negative leader-employee interactions have a negative influence on the employees' satisfaction, which results in signs of stress and unwillingness to go to work. Tsai [65], Hashemi and Sadeqi [41], Ángel Calderón Molina et al [66], and Ahmad et al [67] predict that the organizational climate has a significant effect on job satisfaction. In this paper, we introduce work style as a mediator.…”
Section: Mediator Between Organizational Climate and Job Satisfactionmentioning
confidence: 99%
“…For example, Chen & Spector (1991), Brockner (1988) and De Cremer (2003) have shown that negative leader-employee interactions have a negative influence on the employees' satisfaction, resulting in signs of stress and unwillingness to go to work. Tsai (2014), Hashemi & Sadeqi (2016), Molina et al (2014) and Ahmad, et al (2018) findings propagate that organizational climate has a significant effect on job satisfaction. In this paper, we introduce work style as a mediator.…”
Section: Mediator Between Organizational Climate and Job Satisfactionmentioning
confidence: 85%
“…Organizational climate is acknowledged as a significant structure in organizational behaviour and strategic human resource management. Moreover, it is one of the most important antecedents of person's attitudes and behaviours in business (Ahmad, Jasimuddin, & Kee 2018;Srivastav, 2010). Behaviours and priorities of the team members shape their performance (Bamel, Rangnekar, Stokes, & Rastogi, 2013).…”
Section: Team Climate and Team Performancementioning
confidence: 99%